Reconstruction of the Limits of Advocates' Immunity Rights in Assistance in Corruption Cases to Prevent Professional Abuse and Ensure Legal Certainty - Chitto Cumbhadrika; Zainal Arifin Hoesein (Yayasan Pendidikan Tanggui Baimbaian, 2026)
This study aims to analyze the problematic regulation of advocate immunity rights in assisting corruption cases and formulate a reconstruction of the limits of advocate immunity rights based on legal certainty. The study uses a normative juridical method with a statutory and conceptual approach. The results of the study indicate that the regulation of advocate immunity rights, as regulated in Article 16 of Law Number 18 of 2003 concerning Advocates and Constitutional Court Decision Number 26/PUU-XI/2013, still contains unclear norms, particularly regarding the phrase